Charge carrier transport in polyimide with Co nanoparticles formed by ion implantation - Popok, VN; Lukashevich, MG; Lukashevich, SM; Khaibullin, RI; Bazarov, VV (Elsevier, 2004)
Temperature dependence of resistance is studied for polyimide (PI) samples implanted by Co+ ions with fluences of 2.5 x 10(16)-1.25 x 10(17) cm(-2) at ion current densities of 4, 8 and 12 muA cm(-2). It is found that electron transport in the implanted samples originates from radiation-induced changes of the PI and Co nanoparticle formation and it depends dramatically on the ion current density. A variable range hopping mechanism dominates for all fluences at a low ion current density of 4 muA cm(-2) while a transition to a semimetallic type of conductance is observed with an increase in ion current density due to agglomeration of the Co nanoparticles forming a percolation way for the charge carriers. It is shown that both quantum effects of weak localisation and electron-electron interaction give a significant contribution to the transport mechanism. (C) 2004 Elsevier B.V. All rights reserved.
22nd European Conference on Surface Science (ECOSS 22) -- SEP 07-12, 2003 -- Prague, CZECH REPUBLIC
Keywords: ion implantation; electrical transport (conductivity, resistivity, mobility, etc.); cobalt; aromatics